Spatio-temporal variation of environmental variables and aquatic macroinvertebrate assemblages in Lake Nokoué, a RAMSAR site of Benin - ABOU, YOUSSOUF; ODOUNTAN, Hamed Olaniran; de BISTHOVEN, Luc Janssens (My University, 2019)
Environmental characteristics and macroinvertebrate assemblages of Lake Nokoué (Benin) were investigated from September 2014 to July 2016. Seasonal and hydroclimatic changes, as well as anthropogenic activities were the overriding factors affecting environmental variables investigated. Analysis of macroinvertebrate community structure with several indices revealed a community structure changing across seasons and differing between the sites. Mollusca, Crustacea and Polychaeta were most abundant in the dry seasons, especially at sites close to the ocean, whereas Oligochaeta and Insecta (Diptera, Heteroptera, Coleoptera, Odonata and Ephemeroptera) were abundant in the wet seasons, especially during flood periods (short wet season) at the sites receiving fresh water and on roots of macrophytes. A redundancy analysis placed habitat suitability (temperature and macrophytes) and trophic status …
Keywords: biodiversity indices biomonitoring multivariate analysis tropical lagoon